The effect of playing online games on family communication pattern - Firmannandya, Ade; Prasetyo, Bambang Dwi; Safitri, Reza (Faculty of Communications Science, Dr. Soetomo University, 2021)
Current technological developments give games have quality and facilities that are not inferior to other media. One of them is that game players can interact with each other online so that the game is not only used for entertainment but also verbal and non-verbal interactions. Game users today are not only children but also parents who play online games. In fact, online games are also often played between parents or husband and wife. On the other hand, the increase in online gaming activity for the husband who acts as the head of the family can create problems with family communication patterns. This is because the husband has a powerful role in family members. Therefore, these conditions can affect the harmony of the family. This study aims to determine the relationship between playing online games and family communication patterns in terms of intensity, frequency, and motives in married adult men. The data were collected using a questionnaire distributed online to 100 respondents throughout Indonesia. The data obtained were then analysed using the SPSS program. The results showed that playing online games did not affect family communication patterns. Game players have different reasons according to the intensity, frequency, and motive of playing the game so that it does not have a negative effect on family communication patterns. Thus, it can be concluded that online games can positively impact family communication patterns if appropriately implemented.